A Case of Persistent Urogenital Sinus: Pitfalls and challenges in diagnosis - Tan, H.H.; Tan, S.K.; Shunmugan, R.; Zakaria, R.; Zahari, Z. (Sultan Qaboos University, 2018)
Persistent urogenital sinus (PUGS) is a rare anomaly whereby the urinary and genital tracts fail to separate during embryonic development. We report a three-year-old female child who was referred to the Sabah Women & Children Hospital, Sabah, Malaysia, in 2016 with a pelvic mass. She had been born prematurely at 36 gestational weeks via spontaneous vaginal delivery in 2013 and initially misdiagnosed with neurogenic bladder dysfunction. The external genitalia appeared normal and an initial sonogram and repeat micturating cystourethrograms did not indicate any urogenital anomalies. She therefore underwent clean intermittent catheterisation. Three years later, the diagnosis was corrected following the investigation of a persistent cystic mass posterior to the bladder. At this time, a clinical examination of the perineum showed a single opening into the introitus. Magnetic resonance imaging of the pelvis revealed gross hydrocolpos and a genitogram confirmed a diagnosis of PUGS, for which the patient underwent surgical separation of the urinary and genital tracts.